2010
DOI: 10.1182/blood-2010-01-256099
|View full text |Cite
|
Sign up to set email alerts
|

XIAP deficiency: a unique primary immunodeficiency best classified as X-linked familial hemophagocytic lymphohistiocytosis and not as X-linked lymphoproliferative disease

Abstract: X-linked inhibitor of apoptosis (XIAP) deficiency, caused by BIRC4 mutations, is described to cause X-linked lymphoproliferative disease (XLP) phenotypes. However, compared with XLP caused by SLAM-Associated Protein deficiency (SH2D1A mutation), XIAP deficiency was originally observed to be associated with a high incidence of hemophagocytic lymphohistiocytosis (HLH) and a lack of lymphoma, suggesting that classification of XIAP deficiency as a cause of XLP may not be entirely accurate. To further characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
259
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 236 publications
(275 citation statements)
references
References 26 publications
9
259
0
7
Order By: Relevance
“…Patients Pt8 and Pt9 were reported in a previous report as Patient 3 and Patient 9, respectively [5]. All patients showed typical features of HLH, such as persistent fever, cytopenia, liver dysfunction, and hyperferritinemia during the acute phase of HLH.…”
Section: Patientsmentioning
confidence: 84%
See 2 more Smart Citations
“…Patients Pt8 and Pt9 were reported in a previous report as Patient 3 and Patient 9, respectively [5]. All patients showed typical features of HLH, such as persistent fever, cytopenia, liver dysfunction, and hyperferritinemia during the acute phase of HLH.…”
Section: Patientsmentioning
confidence: 84%
“…Flow cytometric and Western blot analysis of intracellular XIAP were performed, as described previously [5,14].…”
Section: Analysis Of Xiap Mutations and Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 XLP2 is caused by mutations in BIRC4, which encodes XIAP, and has been described as an X-linked form of FHLH. 32 Recent observations suggest that lymphocytes from patients with both types of XLP demonstrate decreased activation-induced apoptosis that contributes to the uncontrolled lymphoproliferation. Taken all together, these genetic disorders still account for less than half of the diagnosed cases of HLH in children, including many familial cases still awaiting molecular definition.…”
Section: Genetic Factors For Mas In Sjiamentioning
confidence: 99%
“…Recently, studies found that loss-of-function mutations in certain gene cause X linked lymphoproliferative disease [65,66]. By using interphase fluorescence in situ hybridization (FISH), Ansell and his colleagues found a novel translocation involving the IGH locus and an unknown partner in a primary MALT lymphoma patient with SS [67].…”
Section: T(x;14)(p11;q32)-igh-gpr34mentioning
confidence: 99%